Uncovering the relationship between trace element exposure, cognitive function, and dietary inflammation index in elderly americans from the National Health and Nutrition Examination Survey 2011-2014 - Chunlan Tang; Min Shen; Hang Hong (BMC, 2024)
Abstract Background The consequences of trace element exposure on cognitive function in elderly adults have been recognized as primarily attributed to the inflammatory response. It is noteworthy that diet can either exacerbate or reduce the inflammatory response. Despite this, there have been limited studies about the effects of diet on the relationship between trace element exposure and cognitive function. Methods A cross-sectional study utilized data from the 2011-2014 NHANES survey to explore the association between trace element exposure and cognitive function in elderly adults. The study enrolled 1726 participants, and generalized linear regression model (GLM), Bayesian kernel machine regression model (BKMR), weighted quantile sum regression (WQS), and quantile g-computation regression analysis (Qg-comp) were conducted to assess the impact of five trace elements (lead, cadmium, mercury, manganese, and selenium) in blood on cognitive function under the anti-inflammatory and pro-inflammatory diet. Results The GLM analysis showed a positive correlation between selenium (Se) and both the instant recall test (IRT) and digit symbol substitution test (DSST) (β = 2.06, 95% CI: 0.70 ~ 3.41; and β = 6.41, 95% CI: 2.35 ~ 10.46, respectively). In contrast, cadmium (Cd) was negatively associated with DSST (β = -1.17, 95% CI: -2.13~ -0.22), and lead (Pb) was negatively associated with IRT (β = -0.47, 95% CI: -0.82~ -0.11). For the animal fluency test (AFT), the highest quartile of manganese (Mn) was negatively associated with the lowest quartile (β = -0.72, 95% CI: -1.34~-0.10), while mercury (Hg) showed no significant associations with cognitive function tests. Subgroup analysis revealed the effects of Cd on IRT and DSST and Se on DSST under the pro-inflammatory diet. Furthermore, The BKMR analysis showed an inverted U-shaped curve with the negative impact of trace element mixtures and DSST and a linearly negative trend with IRT in the pro-inflammatory diet. Among them, Cd was emphasized as the most potent risk factor, and Se was the most vital protective factor for IRT and DSST in WQS and Qg-comp analysis. Conclusions The study suggests that a high-quality diet might alleviate the adverse effects of Cd on IRT and DSST. High Se levels were also associated with better IRT and DSST scores in the pro-inflammatory diet. These findings provide valuable insights into the connection between diet, trace element exposure, and cognitive function in elderly adults.